1999
DOI: 10.1163/156856299x00612
|View full text |Cite
|
Sign up to set email alerts
|

Commercial polyurethanes: The potential influence of auxiliary chemicals on the biodegradation process

Abstract: This investigation elucidates some aspects of auxiliary chemicals on the biodegradation of two commercial polyurethanes (Pellethane and Corethane). The materials were incubated for 28 days with cholesterol esterase and/or with phosphatidylcholine. Extraction studies were carried out on the two materials, using different solvents, chosen on the basis of solvent polarity. FT-IR spectra for the extracted materials indicated the presence of poly(methylene)n oxide moities, silicone oil, bis-ethylene-stearamide, aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…There have been very few studies that have investigated the hydrolytic degradation of polycarbonate‐based polyurethanes. In one study by Vermette et al,25 it was found that MDA was released from Corethane after treatment with CE.…”
Section: Introductionmentioning
confidence: 99%
“…There have been very few studies that have investigated the hydrolytic degradation of polycarbonate‐based polyurethanes. In one study by Vermette et al,25 it was found that MDA was released from Corethane after treatment with CE.…”
Section: Introductionmentioning
confidence: 99%
“…[10] A new class of polycarbonate-based polyurethanes has attracted interest in the field of biomaterials due in part to their mechanical properties similar to those of conventional polyurethanes and to a relatively enhanced hydrolytic stability and oxidative stability. [11][12][13][14][15][16] Recently, it was reported that polycarbonate-based polyurethane materials have a strong sensitivity towards hydrolysis when changes are made to their hard segment content or chemistry or both. [17] In this report, a biodegradable low-molecular weight diurethanediol was combined with the carbonate linkage Summary: Novel enzymatically recyclable poly(carbonateurethane) consisting of a diurethane moiety as a hard segment and a carbonate linkage as an enzymatically cleavable unit was prepared by the polycondensation of biodegradable diurethanediol and diethyl carbonate using lipase.…”
Section: Introductionmentioning
confidence: 99%
“…Du¿e znaczenie ma te¿ mo¿liwooeae sterowania w³aoeciwooeciami materia³ów PUR na drodze dobierania substratów oraz parametrów procesu wytwarzania [2]. Unikatowe cechy fizyczne i mechaniczne oraz du¿a biozgodnooeae powoduj¹, ¿e s¹ to jedne z najbardziej atrakcyjnych materia³ów stosowanych w biomedycynie jako: zastawki serca, przewody rozruszników, cewniki, protezy twarzy oraz nooeniki genów [3]. Poliuretany cechuj¹ siê ponadto ma³¹ trombogennooeci¹ oraz korzystn¹ porêcznooeci¹ chirurgiczn¹.…”
unclassified